Prevalence, diagnostic methods, and clinical outcomes of wasting/cachexia among pediatric cancer patients in Africa: A protocol for a systematic review and meta-analysis - Ivaan Pitua; Daisy Wannyana; Derrick Bary Abila; Felix Bongomin (PLoS ONE, 2026)
Introduction Pediatric cancer is an emerging public health priority in Africa, where survival rates remain critically low compared to high-income regions. Malnutrition; specifically wasting and cachexia; is the most prevalent, yet modifiable comorbidity that compromises treatment tolerance and increases mortality. Recent primary studies from 2025 indicate a significant discrepancy between wasting diagnosed via clinical assessment versus anthropometrically defined wasting, suggesting a “hidden burden” of malnutrition in African oncology wards. However, no comprehensive synthesis of data exists regarding the prevalence of wasting across the continent using modern assessment standards, nor its specific impact on clinical outcomes in the current treatment era. Methods and analysis We will conduct a systematic review and meta-analysis of observational studies (cross-sectional, cohort, and case-control) published from January 1, 2000, to the present. Data sources will include PubMed/MEDLINE, EMBASE, Web of Science and CINAHL. We will include studies involving children and adolescents (0–19 years) diagnosed with malignancies in African healthcare settings. Two independent reviewers will screen studies, extract data, and assess risk of bias using Covidence systematic review software. The risk of bias will be assessed using the Joanna Briggs Institute (JBI) critical appraisal tools. The primary outcome will be the pooled prevalence of wasting/cachexia. Secondary outcomes will include diagnostic accuracy of assessment methods (such as Mid-Upper Arm Circumference [MUAC] vs. Weight-for-Height vs. clinical assessment) and associations with adverse clinical events (neutropenia, sepsis, treatment abandonment, and mortality). A random-effects meta-analysis will be performed using R software. Heterogeneity will be assessed using the I 2 statistic and explored via subgroup analyses (region, tumor type, and assessment tool). Ethics and dissemination Ethical approval is not required as this study relies on secondary data. Findings will be disseminated through a peer-reviewed publication and conference presentations to inform nutritional guidelines for pediatric oncology in resource-limited settings. PROSPERO Registration Number Registration Number: CRD420251237859